University scientific production: challenges for the generation of knowledge and educational practice - Huaire-Inacio, Edson Jorge (2025)
Introduction: scientific production in the field of education, especially in Peru, is not yet a common practice, most teachers do not have scientific production, so it is necessary to know the reasons. Objective: to interpret the factors that  are associated with scientific production in university teachers. Method: the study has a qualitative approach with a constructivist perspective in which four teachers who do not conduct research, four teachers who sporadically research and four research teachers participated; the data were collected through a semi-structured interview guide. Results: five important categories were identified: reasons for publishing, in which the direct and indirect beneficiaries of the research results are identified; resources for research, the internal and external resources that teachers have are analyzed; knowledge and strategies for publishing, the theoretical and practical knowledge they have to write and publish are analyzed; work and networks, the participation or membership of teachers to research teams and networks at national and international level is analyzed; and difficulties in producing, the limitations that teachers have to carry out their research work are identified and analyzed. Discussion: University institutions are responsible for managing the resources necessary to improve scientific production in teachers and the quality of teaching in classrooms.